2012
DOI: 10.3346/jkms.2012.27.7.799
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognostic Factors in Early-Onset Alopecia Totalis and Alopecia Universalis

Abstract: Alopecia totalis (AT) and alopecia universalis (AU), severe forms of alopecia areata (AA), show distinguishable clinical characteristics from those of patch AA. In this study, we investigated the clinical characteristics of AT/AU according to the onset age. Based on the onset age around adolescence (< or ≥ 13 yr), 108 patients were classified in an early-onset group and the other 179 patients in a late-onset group. We found that more patients in the early-onset group had a family history of AA, nail dystrophy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 17 publications
6
38
0
1
Order By: Relevance
“…Three cross-sectional studies regarding asthma and hair loss with a total 1,600 patients reported the prevalence of asthma among AA patients of 1.34–14.5%; however there was no reported association with early onset of AA or development of alopecia totalis or universalis [20, 31, 32]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three cross-sectional studies regarding asthma and hair loss with a total 1,600 patients reported the prevalence of asthma among AA patients of 1.34–14.5%; however there was no reported association with early onset of AA or development of alopecia totalis or universalis [20, 31, 32]. …”
Section: Resultsmentioning
confidence: 99%
“…Of note, a late age of AA onset (> 50 years) is a major confounding variable associated with a significantly reduced prevalence of AA and atopy [17, 18, 20, 21]. For example, one cross-sectional study of Taiwanese late-onset AA patients ( n = 73) reported no association with currently active disease or personal or family history of atopy [18], while another Israeli study ( n = 29) reported a prevalence of atopy in 6.90% of late-onset AA patients [17], Interestingly, juvenile AA (< 16 years) may be associated with a more severe disease course than that of patients with disease onset after 16 years of age [16].…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that AA onset before puberty implies its worse prognosis [23,24]. Accordingly, several studies reported that in comparison to patients with patch AA, patients with AT or AU were younger at the age of onset, had positive family history for AA and more likely had concomitant, autoimmune disorders [24,25]. Our patient had early-onset of AA with early progression to AT and concomitant autoimmune disease, but her family history was unremarkable.…”
Section: Discussionmentioning
confidence: 67%
“…Alopecia areata is a disease of very broad spectrum and only 10% of patients with its severe forms (alopecia totalis-AT and alopecia universalis-AU) could expect full recovery [23]. It is believed that AA onset before puberty implies its worse prognosis [23,24]. Accordingly, several studies reported that in comparison to patients with patch AA, patients with AT or AU were younger at the age of onset, had positive family history for AA and more likely had concomitant, autoimmune disorders [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…[19] However, a study of patients with alopecia totalis and alopecia universalis found no statistically significant association between hair loss and treatment modalities in patients with disease onset below and above 13 years of age. [20] We did not find a statistically significant relationship between age of onset and treatment response.…”
Section: Discussionmentioning
confidence: 82%